Advertisement Remove all ads

Find What the Following Equation Become When the Origin is Shifted to the Point (1, 1). Xy − X − Y + 1 = 0 - Mathematics

Sum

Find what the following equation become when the origin is shifted to the point (1, 1).
xy − x − y + 1 = 0

Advertisement Remove all ads

Solution

 Substituting \[x = X + 1, y = Y + 1\] in the given equation, we get:
\[\left( X + 1 \right)\left( Y + 1 \right) - \left( X + 1 \right) - \left( Y + 1 \right) + 1 = 0\]
\[ \Rightarrow XY + X + Y + 1 - X - 1 - Y - 1 + 1\]
\[ \Rightarrow XY = 0\]
Hence, the transformed equation is  xy = 0.

Concept: Brief Review of Cartesian System of Rectanglar Co-ordinates
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 22 Brief review of cartesian system of rectangular co-ordinates
Exercise 22.3 | Q 3.3 | Page 21
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×